2018
DOI: 10.1002/adhm.201800263
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles Locally Deliver Active Interleukin‐1 Receptor Antagonist In Vivo

Abstract: Despite significant research in therapeutic protein delivery, localized and sustained delivery of active therapeutic proteins remains a challenge. Delivery is a particular challenge for therapeutic proteins with a short half-life. Herein, localized delivery of interleukin-1 receptor antagonist (IL-1Ra) by mineral coated microparticles (MPs) is assessed in a healing rat medial collateral ligament (MCL). The local tissue concentration and systemic serum concentration of IL-1Ra, the anti-inflammatory activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…Previously, researchers have demonstrated that either 5 μg/cm 2 daily doses( 37 ) or a sustained release of 7 to 14 μg/cm 2 of bFGF from a scaffold ( 38 40 ) was required to improve outcomes in this murine model of diabetic wound healing and that increased bFGF dosage showed no improvement or worse outcomes ( 38 , 39 ). As we have previously demonstrated that these mineral coatings are capable of sustained delivery of a variety of growth factors ( 27 , 28 , 41 43 ), including bFGF ( 14 ), we selected 5 μg of sustained delivery from MCMs as an experimental condition to allow for comparison of single-dose mRNA therapy versus recombinant protein therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, researchers have demonstrated that either 5 μg/cm 2 daily doses( 37 ) or a sustained release of 7 to 14 μg/cm 2 of bFGF from a scaffold ( 38 40 ) was required to improve outcomes in this murine model of diabetic wound healing and that increased bFGF dosage showed no improvement or worse outcomes ( 38 , 39 ). As we have previously demonstrated that these mineral coatings are capable of sustained delivery of a variety of growth factors ( 27 , 28 , 41 43 ), including bFGF ( 14 ), we selected 5 μg of sustained delivery from MCMs as an experimental condition to allow for comparison of single-dose mRNA therapy versus recombinant protein therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expected time to complete closure with CM-mRNA + MCM treatment in this model indicated that MCMs offer significant increase in potential therapeutic utility of mRNA delivery. As we have previously demonstrated, the promiscuous electrostatic binding of mineral coatings allows for sustained release of a range of other growth factors, cytokines, and enzymes, including bone morphogenetic protein–2 ( 27 , 45 ), vascular endothelial growth factor ( 14 , 27 , 43 ), interleukin-1RA (IL-1RA) ( 41 ), IL-10 ( 46 ), NT-3 (neurotrophin-3) ( 42 ), and chondroitinase ABC ( 47 ). Therefore, our MCM-mediated overexpress and sequester approach may have broad potential in therapeutic applications where in situ production and retention of highly bioactive secreted proteins would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In this manuscript, we described the use of modied simulated body uid (mSBF) and sequential sequestrations to incorporate BMP2 and VEGF into mineralized collagen scaffolds. This work seeks to adapt promising results using mSBF to deposit a mineral layer that can sequester growth factors onto surfaces [58][59][60][61][62][63][64] to selectively incorporate growth factors used for bone repair applications into three-dimensional, porous biomaterials. Our primary goal is to improve growth factor incorporation and retention into mineralized collagen scaffolds via sequential sequestration strategies to enhance in vivo bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Modied simulated body uid (mSBF) was made according to previous recipes. [58][59][60][61][62][63][64] Briey, 1.41 mM sodium chloride (NaCl, Sigma Aldrich), 4.0 mM potassium chloride (KCl, Sigma Aldrich), 0.5 mM magnesium sulfate (MgSO 4 , Sigma Aldrich), 1.0 mM magnesium chloride (MgCl 2 , Sigma Aldrich), 5.0 mM calcium chloride (CaCl 2 , Sigma Aldrich), 1.0 mM potassium phosphate (KH 2 PO 4 , Sigma Aldrich), and 4.2 mM sodium carbonate (NaHCO 3 , Sigma Aldrich) were dissolved in deionized water and sterile ltered through a MilliporeSigma Stericup with a 0.22 mm lter (Fisher Scientic, Hampton, New Hampshire USA). mSBF was stored at 4 C until use.…”
Section: Modied Simulated Body Uid Preparationmentioning
confidence: 99%
See 1 more Smart Citation